Pilonidální sinus - možnosti operačního řešení - Orhalmi, J; Sotona, O; Dušek, T; Ferko, A (Rozhledy v chirurgii, 2014)
INTRODUCTION: Pilonidal sinus is a skin disease affecting the sacrococcygeal region caused by chronic irritation of the skin by ingrowing hairs that get pushed into skin sinuses and follicles. The acute form of the disease which is presented by subcutaneous abscesses very often develops into chronic suppurative subcutaneous fistula. The incidence of pilonidal sinus is approximately 26/100,000 people. Radical surgical excision using skin flaps is essential for successful treatment. MATERIALS AND METHODS: The results of surgical treatment were analysed retrospectively. All surgical procedures evaluated were performed at the Department of Surgery, University Hospital in Hradec Kralove, from January 2010 to June 2014. The parameters analysed were gender, age, method used to close the defect, length of hospital stay, overall morbidity including pilonidal sinuses recurrence. RESULTS: 141 patients undergoing radical excision for pilonidal sinus were analysed. Primary suture was used in 101 (71.6%) patients. Limberg flap reconstruction was performed in 16 (11.3%) patients and Karydakis procedure was used in 24 (17.0%) patients. The length of hospital stay was 4.2 days. 19 operations were performed for recurrent pilonidal sinus. Norecurrence occurred after Karydakis procedure, there were 3 cases of recurrence after Limberg flap reconstruction, and 8 patients experienced recurrence after primary suture. The overall incidence of recurrence was 7.8%. Surgical site complications were recorded mostly after primary suture (37 patients, 26.2%). Conversely, surgical site complications appeared in the Limberg flap group in 2 patients (12.5%) and in theKarydakis procedure group in 1 patient (4.2%). CONCLUSION: Limberg flap reconstruction and Karydakis procedure lead to better results in pilonidal sinus surgery, especially as regards lower recurrence rates and overall morbidity. Both of these procedures are relatively easy to perform and technically undemanding.
Keywords: pilonidální sinus; lidé; mladiství; výsledek terapie; Adult; Middle Aged; Female; Surgical Flaps; retrospektivní studie; Adolescent; Humans; lidé středního věku; mužské pohlaví; mladý dospělý; Sacrococcygeal Region; ženské pohlaví; Pilonidal Sinus; Young Adult; Treatment Outcome; Male; Plastic Surgery Procedures; Retrospective Studies; sakrokokcygeální krajina; dospělí; zákroky plastické chirurgie; chirurgické laloky